Portraying Critical and Creative Thinking Skills of Chemistry Teachers Candidate in Biochemistry Laboratory Activity - Unwakoly, Semuel; ., Liliasari; SH Munawaroh, Heli (KnE Social Sciences, 2024)
Critical and creative thinking skills are two important aspects that must be exerted to prepare globally competent chemistry teacher candidates. Developing global competence is about how to see teaching practice using a new lens. Minimizing the role of lecturer and making students more active through experimental activities can facilitate the development of both critical and creative thinking skills. Therefore, this study aims to picture the critical and creative thinking skills of chemistry teacher candidates and their motivation in biochemistry laboratory. This case study research involved 38 students’ chemistry teacher candidates as research participants. The data was collected through curriculum document analysis, observations, interviews, and tests for measuring critical and creative thinking skills in biochemistry laboratory activities. Curriculum analysis revealed that the majority of the procedures used in biochemistry laboratories are in cookbook lab-style format. A step-by-step laboratory procedure with a dominant expository method was observed during the teaching process, which was designed to develop only critical thinking skills. The results indicate that critical and creative thinking skills in biochemistry laboratory activities are at a low level, with the average scores obtained through the tests are 45.20% and 33.80%, respectively. Students’ motivation to study in the laboratory was found at a moderate level of 68.00%, suggesting a moderate desire to learn and the satisfaction experienced in the learning process and learning outcome. Keywords: portraying critical, creative thinking skills, biochemistry laboratory activity